Sisŏn nŏmŏ If you were me 5 - Kang, I-kwan; Pu, Chi-yŏng; Kim, Tae-sung; Yun, Sŏng-hyŏn; Sin, Tong-il; Kim, Hyŏn-ju; Pak, Chŏng-uk; Yi, Chŏng-ŭn; Kim, Chin-gŭn; Sim, I-yŏng; Kukka Inkwŏn Wiwŏnhoe; Indie Story; et al. (DS Media, 2012)
"If You Were Me 5 is an innovative omnibus film project to promote tolerance and human rights and shed light on the hardships disadvantaged people face in Korea."---YesAsia.